The botany of the Antarctic voyage of H.M. discovery ships Erebus and Terror in the years 1839-1843 : under the command of Captain Sir James Clark Ross - Hooker, Joseph Dalton, Sir, 1817-1911. ([Weinheim : J. Cramer, 1963)
Facsimile of 1847 edition. I. Flora antarctica.--II. Flora Novae-Zelandiae.--III. Flora Tasmaniae.--[Atlas] Plates. Mode of access: Internet. Biomed's copy: v.1-3 in circulating stacks; atlas in Rare stacks (ask at Biomed History Division office).